Molecular Epidemiological Analysis of Mycoplasma bovis Isolates from the United Kingdom Shows Two Genetically Distinct Clusters - McAuliffe, Laura (American Society for Microbiology, 2004)
Mycoplasma bovis is an important veterinary pathogen causing pneumonia, arthritis, and mastitis in infected cattle. We investigated the genetic diversity of 53 isolates collected in the United Kingdom between 1996 and 2002 with pulsed-field gel electrophoresis (PFGE), amplified fragment length polymorphism (AFLP), and random amplified polymorphic DNA (RAPD) analysis. In addition, the influence of variable surface protein (Vsp) profiles on the profiles generated with molecular typing techniques was studied. Both AFLP and RAPD separated the isolates into two distinct groups, but PFGE showed less congruence with the other techniques. There was no clear relationship between the geographic origin or year of isolation of the isolates and the profiles produced. No correlation between Vsp profiles and any of the molecular typing techniques was observed. We propose that RAPD and AFLP provide valuable tools for molecular typing of M. bovis.